Selçuk weather station and web-mobile applications - Fatih BASCIFTCI; Erdem AĞBAHCA; Kubra UYAR; Züleyha YILMAZ ACAR; Burak TEZCAN (International Journal of Applied Methods in Electronics and Computers, 2022)
In this paper, a system for reading meteorological data like temperature, humidity, air pressure, wind speed, wind direction, and rainfall at regular intervals, deployed in Selçuk University Alaeddin Keykubat Campus. The system also provides real-time images and video time-lapses of the campus sky. These data are made available to university people via a website and mobile applications for both iOS and Android. The website and mobile applications provide a clear experience for the users, also explaining the icons and terms used on the website. Users can access the system archive in graphical ways.